Call the midwife. Season seven [videorecording (DVD)] - Agutter, Jenny; Bassett, Linda; Parfitt, Judy, 1935-; Worth, Jennifer, 1935-2011 (BBC, 2018)
"In the old houses and bold new apartment buildings of 1963 London, expectant mothers need more help than ever from the nuns and nurses of Nonnatus House"--Container.